2022
DOI: 10.1002/chem.202201385
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Synthesis of the Bioactive Fragment of Salbutamol and Derivatives in a Self‐Optimizing Flow Chemistry Platform

Abstract: The implementation of self‐optimizing flow reactors has been mostly limited to model reactions or known synthesis routes. In this work, a self‐optimizing flow photochemistry platform is used to develop an original synthesis of the bioactive fragment of Salbutamol and derivatives. The key photochemical steps for the construction of the aryl vicinyl amino alcohol moiety consist of a C−C bond forming reaction followed by an unprecedented, high yielding (>80 %), benzylic oxidative cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…415 415 Middle: Photocatalytic two-step synthesis of a 2-oxazolidinone derivative performed by Jensen and co-workers. 426 Bottom: Two-step synthesis of lidocaine by Ley and co-workers. 116 From a practical standpoint, maximizing the yield alone is not a sufficient criterion for successful synthesis-the product needs to be isolated from the crude reaction mixture in high purity, which is usually achieved through phase transfers and phase separations (e.g., extraction, filtration, chromatography).…”
Section: Sequential Single-step Optimizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…415 415 Middle: Photocatalytic two-step synthesis of a 2-oxazolidinone derivative performed by Jensen and co-workers. 426 Bottom: Two-step synthesis of lidocaine by Ley and co-workers. 116 From a practical standpoint, maximizing the yield alone is not a sufficient criterion for successful synthesis-the product needs to be isolated from the crude reaction mixture in high purity, which is usually achieved through phase transfers and phase separations (e.g., extraction, filtration, chromatography).…”
Section: Sequential Single-step Optimizationsmentioning
confidence: 99%
“…Top: Exemplary synthesis of PyOx ligands by Felpin and co-workers 415. Middle: Photocatalytic two-step synthesis of a 2-oxazolidinone derivative performed by Jensen and co-workers 426. Bottom: Two-step synthesis of lidocaine by Ley and co-workers 116.…”
mentioning
confidence: 99%
“…In recent years, the screening of photochemical reactions in flow has experienced impressive progress, with advances in reagent solutions preparation and handling, photoreactor design, analysis, automated operation, and optimization algorithms. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Eyke et al reported an automated multiphase platform equipped with 10 parallel reactor channels out of which a channel was adapted to screen photochemical reactions by integrating an LED board 3 . Moreover, a robotic platform with a capillary reactor irradiated by 6 LED modules was reported by Slattery et al 4 Considerably fewer studies described screening platforms in which heterogeneous photocatalysts are involved as slurry 10 , imprinted polymer nanoparticles 17 and immobilized on glass beads 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted on the flow synthesis of APIs, including ibuprofen (a widely used painkiller), , artemisinin (an antimalaria drug), olanzapine (an atypical antipsychotic), efavirenz (a drug against the human immunodeficiency virus), and rolipram (an anti-inflammatory drug) . More recent examples are lomustine (a drug for treatment of brain tumors), dolutegravir (an anti-HIV drug), ondansetron (a drug to prevent nausea and vomiting caused by cancer chemotherapy), and a bioactive fragment of salbutamol (an asthma medication) …”
Section: Introductionmentioning
confidence: 99%
“…16 More recent examples are lomustine (a drug for treatment of brain tumors), 17 dolutegravir (an anti-HIV drug), 18 ondanse-tron (a drug to prevent nausea and vomiting caused by cancer chemotherapy), 19 and a bioactive fragment of salbutamol (an asthma medication). 20 Given the limited time available for process design in the pharmaceutical industry, 21 a modeling and simulation approach can be advantageous. Mechanistic models, which are based on an explicit understanding of reaction mechanisms, provide a reliable method for understanding complex systems, process design, evaluation, and optimization.…”
Section: ■ Introductionmentioning
confidence: 99%